Heavy metal ions incorporated within strippable PVA-TTA polymeric matrix detected by colorimetry and vibrational spectroscopies - Shahar Aziza; Smadar Attia; Svetlana Gelfer; Ofra Paz Tal (Results in Materials, 2023)
We report the synthesis and characterization of a novel strippable polymeric matrix of polyvinyl alcohol (PVA) aqueous solutions embedded with 2-thenoyl trifluoroacetone (TTA) organic ligand for decontamination of heavy metal ions. The TTA-containing polymeric matrix was applied to several contaminated surfaces comprising various concentrations of UO22+, Cu2+, Fe3+ and Cs+ contaminants. Except for Cs+, the contaminants were found to interact with the ligand contained in the polymeric matrix, accompanied by a consequent indicative strong color change, specific to the metal contaminant. The dried coating is easily exfoliated leaving the surface decontaminated. ATR-IR and Raman spectroscopies were also applied, showing a clear spectroscopic signature of each metal contaminant, in particular when contained in a mixed ion solution. All in all, the utilization of vibrational spectroscopies is shown to provide important complementary detection signatures that are otherwise vague when surfaces comprising trace amounts of contaminants, lacking color responsive behavior, are involved.